1994
DOI: 10.1212/wnl.44.7.1325
|View full text |Cite
|
Sign up to set email alerts
|

[ 11 C]raclopride and positron emission tomography in previously untreated patients with Parkinson's disease

Abstract: We studied cerebral dopamine D2-receptor binding using [11C]raclopride and PET in 18 previously untreated patients with Parkinson's disease (PD) and 14 healthy volunteer subjects. Sixteen patients were scanned before and after 3 to 4 months of stable oral therapy with either L-dopa (300 mg/d) (n = 7) or lisuride (0.8 to 1.2 mg/d) (n = 9). Two additional patients were investigated before and after a continuous IV infusion of L-dopa. In addition, we studied the effect of acute IV L-dopa and lisuride administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
121
0
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(132 citation statements)
references
References 0 publications
10
121
0
1
Order By: Relevance
“…71 Serial 11 C-raclopride PET has shown that after 6 months of exposure to levodopa the mildly increased putamen 11 Craclopride binding seen in de novo PD patients subsequently normalizes. 73 Chronically levodopa-exposed PD cases continue to show normal levels of putamen D2 binding, explaining their good locomotor response to levodopa. 74 11 C-SCH23390 PET, a marker of D1 site binding, has revealed normal striatal uptake in de novo PD, 74 whereas patients who had been exposed to levodopa for several years showed a 20% reduction in striatal binding.…”
Section: Fluctuations and Dyskinesiasmentioning
confidence: 99%
“…71 Serial 11 C-raclopride PET has shown that after 6 months of exposure to levodopa the mildly increased putamen 11 Craclopride binding seen in de novo PD patients subsequently normalizes. 73 Chronically levodopa-exposed PD cases continue to show normal levels of putamen D2 binding, explaining their good locomotor response to levodopa. 74 11 C-SCH23390 PET, a marker of D1 site binding, has revealed normal striatal uptake in de novo PD, 74 whereas patients who had been exposed to levodopa for several years showed a 20% reduction in striatal binding.…”
Section: Fluctuations and Dyskinesiasmentioning
confidence: 99%
“…After its intravenous administration 18 F-dopa is taken up by the terminals of dopaminergic projections and stored as 18 F-dopamine and its metabolites. 1 The rate of striatal 18 F accumulation reflects both 18 F-dopa transport into striatal dopamine vesicles and its decarboxylation by dopa decarboxylase (DDC).…”
Section: The Presynaptic Dopaminergic Systemmentioning
confidence: 99%
“…After its intravenous administration 18 F-dopa is taken up by the terminals of dopaminergic projections and stored as 18 F-dopamine and its metabolites. 1 The rate of striatal 18 F accumulation reflects both 18 F-dopa transport into striatal dopamine vesicles and its decarboxylation by dopa decarboxylase (DDC). Within the 90 min of a conventional 18 F-dopa PET scan, striatal 18 F uptake can be regarded as essentially unidirectional and so can be represented kinetically by an influx constant, K i .…”
Section: The Presynaptic Dopaminergic Systemmentioning
confidence: 99%
See 2 more Smart Citations